Coefficient Bounds for Bi-Univalent Functions With Ruscheweyh Derivative and Sălăgean Operator - Patil, Amruta; Khairnar, S. M. (Communications in Mathematics and Applications, 2023)
This paper inaugurate two subclasses of bi-univalent functions on open unit disk \(Δ\) and obtain estimates on the initial coefficient for the functions in these subclasses by using Sălăgean and Ruscheweyh differential operators.
Keywords: Univalent functions; Bi-univalent function; Starlike and convex functions